1990
DOI: 10.1353/aad.2012.0498
|View full text |Cite
|
Sign up to set email alerts
|

Total Communication Use Among Elementary Teachers of Hearing-Impaired Children

Abstract: This study examined the degree to which teachers' signed Manually Coded English messages represented their spoken utterances. Results indicate that educators in early elementary programs can, and do, provide a complete manual representation of their spoken English messages. This is in contrast with earlier research with middle school educators and parents of hearing-impaired children. Findings indicate that MCE proficiency may be influenced both by teacher attitude regarding the importance of signing a complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Participants 1 and 5 used freestanding objects that were stored in a box. Two participants (Participants 6 and 9) were introduced to total communication, a communication approach that is commonly used with children with hearing impairment ( Mayer & Lowenbraun, 1990 ), and that emphasizes the flexible use of communication across modalities. Participant 3 used two communication boards displaying pictorial representations of important people, things and activities.…”
Section: Methodsmentioning
confidence: 99%
“…Participants 1 and 5 used freestanding objects that were stored in a box. Two participants (Participants 6 and 9) were introduced to total communication, a communication approach that is commonly used with children with hearing impairment ( Mayer & Lowenbraun, 1990 ), and that emphasizes the flexible use of communication across modalities. Participant 3 used two communication boards displaying pictorial representations of important people, things and activities.…”
Section: Methodsmentioning
confidence: 99%
“…The teachers in the Luetke-Stahlman study were able to retain the semantic meaning of their voiced message in 89% of their signed productions, and Wodlinger-Cohen's teachers were accurate 88% of the time. These studies would indicate that teachers' MCE skills vary widely, and that propositional intactness is not necessarily related to the exact representation of speech via signing (see also Mayer & Lowenbraun, 1989;Stewart, Akamatsu, & Bonkowski, 1988). It is also clear that deaf children probably see a great deal of signing that does not accurately represent English, regardless of good intentions.…”
mentioning
confidence: 99%
“…Although these studies sought to determine the match between signs and speech during simultaneous communication, they suggested that teachers' signed productions resulted in sentence structures that were also not grammatically correct ASL. On the other hand, in a recent study by Mayer and Lowenbraun (1990), teachers demonstrated the ability to manually code a high percentage of English morphemes (range = 93% to 98%) when their implementation of a signing policy was supervised monthly.…”
Section: Teachers Use Of Signsmentioning
confidence: 99%
“…Some of the major concerns are the possible effects of teachers who do not completely code a language (i.e., English or ASL) during their signed instructions (Luetke-Stahlman, 1988a, 1988b, 1988c; the ability of teachers to sign and speak simultaneously (Bernstein et al, 1985;Mayer & Lowenbraun, 1990;Strong & Charlson, 1987); the absence of ASL from total communication programs (e.g., Commission on Education of the Deaf, 1988;Stewart, 1982); and the number of teachers who actually use an English sign system or ASL during their classroom interactions (Woodward & Allen, 1987. Underlying each of these concerns is the proposition that the level of proficiency of teachers' signing may be a critical factor in determining the academic success of their students.…”
mentioning
confidence: 99%